ANALISIS PENGARUH DIMENSI KUALITAS LAYANAN CUSTOMER SERVICE TERHADAP KEPUASAN NASABAH TABUNGAN PRESMA PADA PD BANK PERKREDITAN RAKYAT BLORA (Studi Kasus Pada PD Bank Perkreditan Rakyat Blora) - Ahlul Trina Hidayanti; Jati Handayani (KEUNIS, 2019)
This study aims to determine the quality factors of Customer Service consists of tangible, reliability, responsiveness, assurance, and empathy toward customer satisfaction PD Bank Perkreditan Rakyat Blora The population are all customers from Tabungan Prema, they are 100 respondent. Testing method of data that used in this study was to test the validity, reliability test, normality test, multicoloniarity test, heteroskesdastisitas test, test analysis linear multiple, F test, t test, and the coefficient of determination (R2 ). wich shows the can used to measure customer satisfaction. multiple linear regression methot yields customer satisfaction equation = 0,246 + 0,295 tangible + 0,318 reliability + 0,208 responsiveness + 2,16 assurance + 0,330 empathy + e. In F test, it is found that dimention of Customer Service there are tangible, reliability, responsiveness, assurance and empathy secara simultaneously have significant effect. The result of t test is influence tangible, reliability, responsiveness, assurance and empathy have significant influence to customer satisfaction Tabungan Presma users of customer service at PD Bank Perkreditan Rakyat Blora